Hoping to Pass: Randomized Trial of a One-Time Hope Intervention on Standardized Exam Passing Rates in BSN Students. (January 2021) - Wedgeworth, Monika L.; Eyer, Joshua C.; March, Alice L.; Feldman, David B.
BACKGROUND: National standardized nursing exams serve as critical measures of student readiness for practice and carry significant consequences for students and academic institutions. Educational interventions that can enhance a student's performance increase the probability of academic success. Previous studies link hope to grade point average in college students and on standardized exam (SE) scores in nursing students, yet it is not clear if hope can be increased utilizing a one-time intervention in ways that produce lasting benefits for passing SEs.AIMS: Aim 1 tested the efficacy of a one-time hope intervention on increasing SE passing rates among BSN nursing students. Aim 2 examined the role of the interventions, selected state-mechanism variables, and trait characteristics in predicting SE passing.METHOD: This comparative-effectiveness trial utilized a randomized, controlled, multiple-cohort experimental design to compare a one-time 90-minute hope intervention to an attention-matched progressive muscle relaxation intervention on SE passing scores among BSN nursing students.RESULTS: Levels of hope briefly increased following the hope intervention. Both interventions demonstrated short-term improvement in state-level psychosocial indicators but did not affect SE scores. Among trait and mechanism factors, only academic self-efficacy was linked with passing SEs.CONCLUSIONS: This study demonstrated that a single-session hope intervention can increase short-term hope. In this sample of 292 BSN students, there was no statistically significant long-term effect on passing SEs; however, this study may lay the groundwork for future interventions investigating booster sessions, or how to modify the intervention for struggling students.